War Hecatomb. International Effects on Public Health, Demography and Mentalities in the 20th Century - Matos, P. T. de; Sardica, José Miguel; Silva, Helena (2019)
War Hecatomb. International Effects on Public Health, Demography and Mentalities in the 20th Century, offers new insights on the impact of wars (namely, but not exclusively, World War I), by underlining its social and psychological consequences, particularly in public health, demography, and mentalities in different countries. Therefore, it is not just another book on World Wars, since it does not focus primarily on political, diplomatic, military or economic aspects. Instead, the work offers a brand new approach on these wars’ consequences, and especially on the civilizational significance of the Great War of 1914-1918. This original view over societies coping with the aftermath of the two world wars reveals how states and different agents were compelled to act and to face the new post-war reality, bringing to light an innovative social agenda while simultaneously trying to cope with the overwhelming phenomenon of physically and mentally scarred multitudes of veterans and their families. The book focuses on the consequences of conflicts in different perspectives and geographic locations. In twelve chapters, several aspects and effects of wars are analysed through different lens. Editors’ PrefaceMassive wars, born out of political radicalisms, harsh nationalisms, mis-conduct diplomacy or generalized socioeconomic strains were a key defin-ing aspect of the 20th century, in Europe and elsewhere. The path “to hell and back” (the title of one of historian Ian Kershaw’s recent books) started in 1914–1918, when the old continent was engulfed by the Great War, later to be called World War I. The overall consequences of that conflict were so profound and widespread, across countries and societies, that there was indeed a civilizational descend until 1945. And in the second half of the century, despite the nuclear deterrence of the Cold War, many other regional armed confrontations amounted. This book, entitled War Heca-tomb. International Effects on Public Health, Demography and Mentalities in the 20th Century, offers new insights on the impact of wars (namely, but not exclusively, World War I), by underlining its social and psychological consequences, particularly in public health, demography, and mentalities in different countries. Therefore, this is not just another book on World Wars, since it does not focus primarily on political, diplomatic, military or economic aspects, as is so often the case. Instead, our work offers a brand new approach on these wars’ consequences, and especially on the civilizational significance of the Great War of 1914–18. This original view over societies coping with the aftermath of the two world wars reveals how states and different agents were compelled to act and to face the new post-war reality, bringing to light an innovative social agenda while simulta-neously trying to cope with the overwhelming phenomenon of physically and mentally scarred multitudes of veterans and their families.The book focuses on the consequences of conflicts in different per-spectives and geographic locations. In twelve chapters, several aspects and effects of wars are analyzed through different lens. Visible and invisible wounds affected soldiers and their households with the spread of diseases and famine, for example. Other health issues, as war prisoners or eugen-ics, are also examined. The demographic consequences of armed conflicts are drawn in studies on civil demographic losses and on populations’ body weight and height. The book also reveals, through a French case-study, the new legal framework drawn back then to protect war orphans. 8 Editors’ PrefaceFollowing a chronological and thematic order, Chapter 1 is a broad-spectrum introduction to what follows. In «From innocence to harshness: the civilizational significance of World War I», José Miguel Sardica underlines how this conflict created a new negative civilizational paradigm in its aftermath, paving the way for an ethos of decadence that shadowed Europe for years. This introduction is followed by other analysis of the Great War. In Chapter 2, «‘Silent Deaths’: British Soldier Suicides in the First World War», Simon Walker documents how suicide was a common, though tragic, strategy of soldiers in the battlefield to escape the horrors of war trenches, anticipating a self-inflicted death, rather than wait-ing to be killed by enemy fire. In Chapter 3, «A Eugenic Legislation: Health before, during and after the Great War in Italy», Emilia Musu-meci studies the disappointment and discussion of eugenicists due to the violence of war that was killing the strongest men.The Great War also shaped modern masculinity and femininity. The specific case of gender identities in Romania is analyzed by Georgeta Fodor and Maria Tătar-Dan in Chapter 4, «‘Our Sacrifice for the Coun-try!’: War and Gender Identity in Transylvania». Next, in Chapter 5, José Manuel Sobral and Maria Luísa Lima present a study titled «Public silence: the memory of the influenza epidemic of 1918–19 in Portugal», focussing on how the war functioned as a spreader of disease worldwide, and exemplifying this using the case of the so-called “Spanish flu” and its effects in neighbouring Portugal, one of the latecomers to the conflict. With an unprecedented number of deaths among soldiers, different forms of assistance were created, including for war orphans. The French case is analyzed by Nicolas Todd on Chapter 6, «The social reception of a novel legal framework for WW1 orphans: the pupille de la Nationstatus». Those men that managed to return home still had to live and cope with their war traumas. Each nation tried somehow to assist them, and in Chapter 7, «War Trauma, mental health and social consequences of World War I in Romanian Psychology and Psychiatry (1919–1939)», Oana Habor examines the Romanian case and the contributions there given to the progress of psychiatrics and psychology. As Sílvia Correia shows in Chapter 8, «“(In)complete Citizens”: First World War Por-tuguese Disabled Soldiers and the Construction of Group Identity», these citizen-soldiers tried to return to civic life in the post-war but were not always able to do so, demanding to be recognized as war victims, in a Editors’ Preface 9struggle both for physical and symbolic healing, not easy to attain in the years immediately following the armistice of 1918. The First World War had a harsh impact on civilians and demography, as the Austrian case-study reveals. Working on this national case, Peter Teibenbacher’s Chapter 9, «War, Peace and times of transition: Civil demographic losses in Austria during WWI and “recovery” until 1938. An international and intraregional comparison», makes an extensive appraisal of the births and deaths losses in Austria comparatively with other countries in the interwar period.Despite the end of the First World War, peace was not a reality for all countries. After the armistice, other conflicts took place, as between Greece and the Ottoman Empire. In Chapter 10, «For the protection of public health: Prisoners of War and Refugees in Quarantine on Saint-George Island, 1922–1925», Anastasios Zografos examines the import-ant measures taken by the Greek government to avoid an epidemic crisis following the country’s defeat and the return of thousands of war prisoners and refugees. The aftermath of World War II also had an enormous effect over population’s health, allowing for comparisons of cohorts a genera-tion apart. Chapter 11, «The impact of the Second World War on the young Polish population», authored by Grażyna Liczbińska, Zbigniew Czapla, Janusz Piontek and Robert M. Malina, focus on the specific case of Poland during this conflict, revealing how famine then endured had a lasting impact on the population height and weight. Chapter 12, «Warfare in the 19th-20th Centuries and Its Effects: A Necessary Evil? (Case Study: World War I)», by Ioan Bolovan and Sorina Paula Bolovan, closes the volume here offered. They do draw major conclusions on war consequences throughout the contemporary age, in a text that serves as a final reflection on the major issues tackled all along the book. Carrying a transnational approach that fosters comparative studies on countries so often neglected by mainstream historiography, War Hec-atomb. International Effects on Public Health, Demography and Mentali-ties in the 20th Century is therefore aimed at academics and researchers. It can be of interest not only to those working on wars and society, but also to those with interest on demography, history of health and mentalities at large, through specialized and wider audiences curious on 20th century social history and war studies. 10 Editors’ PrefaceThis book is partially an output of an international conference, held in the NOVA University of Lisbon, in Portugal, in June 2017, entitled War Hecatomb, and organized within an ongoing funded research pro-ject on Medical and Healthcare services in the First World War: the case of the Portuguese soldiers during and after the Great War (1914–1960)1. Some of the papers there presented were enlarged and transformed into the chapters herewith included; and the Editors invited other colleagues, whose work we believed would fit the scope of this book, to contribute with their specialized research work. This dynamic has already led to a second edition of the War Hecatomb international conference, this time held in Cluj-Napoca, Romania, in June 2018 – and will perhaps allow for a new book publishable in a near future. The Editors are obviously grateful to the Contemporary History Insti-tute (IHC) and to the Humanities Research Centre (CHAM), both belong-ing to the NOVA University of Lisbon, for all the institutional support given to the abovementioned research project and conferences, and for their generous financial contribution towards the publication of this book. An acknowledgement is also due to the Portuguese Commission for Mili-tary History, a governmental organization within the Portuguese Ministry of Defence, which became interested in this volume and also sponsored it.Of the three Editors of the book, one is also a chapter author. Besides our joined efforts, this book would not have been possible without the sci-entific contribution presented by the other seventeen colleagues involved in it, academics who worked closely with us, authoring their texts, review-ing them and offering the community sound historical work. The manu-script was lucky enough to be accepted by the prestigious academic pub-lisher Peter Lang. And thus, a warm thanking should also be given to all those who assisted the Editors at Peter Lang, especially Jana Habermann and Thomas Lemaître, who took care of all the bureaucratic and editorial tasks needed to produce and publish this book. Thank you, also, to Prof. Michel Oris, the coordinator of Peter Lang’s series Population, Famille et Société, the collection of which this book now takes part in, for accepting this contribution and for the support also given to us. Lastly, the Editors wish to pay tribute to Prof. Antoinette Fauve-Chamoux for her advice and encouragement throughout the year